Quality by Design Assisted Optimization and Risk Assessment of Black Cohosh Loaded Ethosomal Gel for Menopause: Investigating Different Formulation and Process Variables - Sradhanjali Mohapatra; Mohd. Aamir Mirza; Sayeed Ahmad; Uzma Farooq; Mohammad Javed Ansari; Kanchan Kohli; Zeenat Iqbal (MDPI AG, 2023)
Black cohosh (Cimicifuga racemosa) (CR) is a popular herb and is medically lauded for ameliorating myriad symptoms associated with menopause. However, its pharmaceutical limitations and non-availability of a patient-compliant drug delivery approach have precluded its prevalent use. Henceforth, the current research premise is aimed at developing an ethosomal gel incorporating triterpene enriched fraction (TEF) obtained from CR and evaluating its effectiveness through the transdermal application. TEF-loaded ethosomes were formulated using solvent injection, optimized and characterised. The optimized ethosomes were then dispersed into a polymeric gel base to form ethosomal gel which was further compared with the conventional gel by in-vitro and ex-vivo experiments. Here, the quality by design (QbD) approach was exploited for the optimization and development of ethosomal gel. The elements of QbD comprising initial risk assessment, design of experimentation (DoE), and model validation for the development of formulation have all been described in detail. The optimized ethosomes (F03) showed a nanometric size range, negative zeta potential and good entrapment. The in vitro release profile of gel revealed a burst release pattern following the Korsmeyer Peppas model having Fickian diffusion. The transdermal flux of ethosomal gel was observed to be more than that of conventional gel. Texture analysis and rheological characterization of the gel, revealed good strength showing shear thinning and pseudoplastic behaviour. The confocal microscope investigation revealed the deeper skin permeation of ethosomal gel than conventional gel. This result was further strengthened by DSC, IR and histological assessment of the animal skin (Wistar rat), treated with the optimized formulation. Conclusively, the implementation of QbD in the formulation resulted in a better understanding of the process and the product. It aids in the reduction of product variability and defects, hence improving product development efficiencies. Additionally, the ethosomal gel was found to be a more effective and successful carrier for TEF than the conventional gel through the transdermal route. Moreover, this demands an appropriate animal study, which is underway, for a stronger outcome.